ANALISIS KOMITMEN MANAJEMEN OPERATOR KAPAL TANKER DALAM MENERAPKAN STANDAR INDUSTRI MIGAS OCIMF TMSA DALAM RANGKA TERCIPTANYA KESELAMATAN PELAYARAN - Dina Kristina Tanjung (Yayasan Pendidikan Medika Indonesia, 2022)
One of the shipping activities is in the oil and gas industry which uses tankers of various sizes. So that shipping traffic is getting crowded which can cause shipping accidents. Therefore, tanker operators must ensure the safety of all people while the tanker is operating in order to create shipping safety by applying the oil and gas industry standard, namely Tanker Management and Self-Assessment (TMSA). This study aims to analyze the management commitment of tanker operators in applying industry standards in order to create shipping safety. This research is a qualitative research on 5 tanker operator companies which analyzed the leadership and safety management system to see how the ship operator management commitment. The results showed that the management commitment of 3 out of 5 companies was not visible. Meanwhile, the management commitment of 2 out of 5 companies is visible. This is known based on the results of the TMSA Element 1 audit, namely leadership and safety management systems. Therefore, tanker operator companies should be able to increase their commitment to create shipping safety.